The timeline of non-vocal and vocal communicative skills in infants with hearing loss - Saksida, Amanda; Rebesco, Roberta; Colombani, Arianna; Pintonello, Sara; Tonon, Eleonora; Santoro, Andrea Martina; Orzan, Eva (Frontiers in Pediatrics, 2024)
Objective: The study investigates what is the link between early verbal and non-vocal abilities, when does predominantly verbal communicative style occur after the intervention with cochlear implants (CI) or hearing aids (HA), and how predictive it is of later linguistic development in deaf and hard of hearing (DHH) infants and children. Methods. Cohort: children with moderate-to-profound hearing impairment (N = 49, 20 girls, mean age at HA or CI intervention = 15 months, range: 4-35 months). Measures: Receptive and productive vocabulary at 24 and 36 months and video analysis at 12 months post-intervention. Analysis: Predictive values of total and verbal responses to communicative turns for later vocabulary development were assessed, as well as the relative time course of the development of vocal/verbal communication in DHH children. Results: Vocabulary at 24 months is predicted by auditory responses at 12 months, as well as by overall responsiveness before intervention. Non-vocal responses decline and overall verbal responses increase significantly between 6 and 12 months after intervention. The trend is delayed in children with delayed (> 12 months of age) treatment with CI or HA. Conclusions: Age of intervention affects the development of vocal/verbal communicative style. Language development, in particular, vocabulary growth, can be further stimulated by the enhancement of preverbal (both vocal and non-vocal) communicative skills.